2020
DOI: 10.1111/grow.12441
|View full text |Cite
|
Sign up to set email alerts
|

Designing regional innovation systems in transitional economies: A creative ecosystem approach

Abstract: Regional Innovation Systems (RIS) have become a policy panacea for states looking to develop their economies. However, much of the research on RIS is from Western developed economies, which have established infrastructures and institutional governance networks. Yet, in transitional economies, the growth rate in some parts of the economy is so rapid that policy makers and institutions are unable to record changes as they occur, including the emergence of new economic sectors, such as the creative industries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…Vietnam is a transitional economy (Gasparin et al, 2020; Gasparin & Quinn, 2020b). Although craft in Vietnam is very important and quite pervasive in establishing local cultures, it is disappearing amidst globalization and rapid development (Gasparin & Quinn, 2020a). The participating designers are keen to develop sustainable growth for ethnic and craft groups based on capacity building, by linking ethnic minorities with designers in the city, in order to create sustainable growth through an ethical supply chain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vietnam is a transitional economy (Gasparin et al, 2020; Gasparin & Quinn, 2020b). Although craft in Vietnam is very important and quite pervasive in establishing local cultures, it is disappearing amidst globalization and rapid development (Gasparin & Quinn, 2020a). The participating designers are keen to develop sustainable growth for ethnic and craft groups based on capacity building, by linking ethnic minorities with designers in the city, in order to create sustainable growth through an ethical supply chain.…”
Section: Methodsmentioning
confidence: 99%
“…Although craft in Vietnam is very important and quite pervasive in establishing local cultures, it is disappearing amidst globalization and rapid development (Gasparin & Quinn, 2020a) The interviews were conducted in English and on two occasions with the help of an interpreter. Informal interviews were first noted in a diary and then digitally transcribed.…”
Section: Data Collectionmentioning
confidence: 99%
“…Gasparin and Quinn’s (2020) paper takes us to Vietnam. The study broadens the ecosystemic thinking by offering a country case study of the creative economy, something relatively new in the ecosystems or systems literature.…”
Section: The Articles In the Special Issuementioning
confidence: 99%
“…All of them add new contexts and insights to the discussion of the systemic approaches to economic development. Gasparin and Quinn's (2020) paper takes us to Vietnam. The study broadens the ecosystemic thinking by offering a country case study of the creative economy, something relatively new in the ecosystems or systems literature.…”
Section: The Articles In the Special Issuementioning
confidence: 99%
“…No specific method has been universally accepted as the best for analyzing and assessing RISs. Different authors have used a broad range of approaches to study RISs; among these approaches are participatory evaluation, network analysis, cluster analysis, data envelopment analysis, qualitative content analysis, case studies, regression models and comparative studies (Stejskal et al , 2018; Avilés-Sacoto et al , 2020; Rodríguez-Soler and Brunet Icart, 2018; Fernández-Serrano et al , 2019; Kofler et al , 2018; Berman et al , 2020; Gasparin and Quinn, 2020; Teng and Chen, 2019; Hajek et al , 2019). Wang et al conducted a thorough review of the literature on RISs and based on their findings, identified four approaches that have been developed to analyze RISs: the structural approach, the functional approach, the effectiveness approach and the triple helix approach.…”
Section: Literature Reviewmentioning
confidence: 99%